A First Attempt into the Production of Acylglycerol Mixtures from Echium Oil - Vázquez, Luis; Jordán, Alejandro; Reglero, Guillermo; Torres, Carlos F. (Frontiers in Bioengineering and Biotechnology, 2016)
Enzymatic glycerolysis of Echium oil (Echium plantagineum) has been carried out in the presence of four commercial lipases. Different pretreatment of the reaction mixture, such as high pressure homogenization and addition of food grade monoolein as an emulsifier, were evaluated to test their influence on the glycerolysis reaction. In addition, the impact of reducing temperature and the utilization of a solvent generally recognized as safe as a flavoring agent, such as limonene, were also investigated. Conversion of ca. 60-70 % of triacylglycerols, and production of ca. 25-30 % of monoacylglycerols were attained. Finally, at the best reaction conditions, the glycerolysis reaction was scaled-up at pilot plant and the product mixture obtained, fractionated via molecular distillation. From this stage, two products were attained: a distillate containing 80 % of monoacylglycerols and a residue containing approximately 50% of diacylglycerols and 50 % of triacylglycerols. All these mixtures can be utilized as self-emulsifying vehicles for the formulation of bioactive substances and also as precursors for the production of structured bioactive lipids.